War contributions during the occupation of Tacna: The Vargas Case (1907) - Céspedes, Rodrigo (Derecho Público Iberoamericano, 2022)
In the case under discussion, the tribunal decides the legitimacy of war contributions during the occupation of Tacna by Chilean forces during the Pacific War (1879-1884). The tribunal bases its decision on the incipient humanitarian law of the time and the customs and principles of international law.